Development of New Edible Biodegradable Films Containing Camu-Camu and Agro-Industry Residue - Naves, Huéberton Barbosa [UNESP]; Stafussa, Ana Paula; Madrona, Grasiele Scaramal; Tanaka, Fabrício Cerizza [UNESP]; Aouada, Fauze Ahmad [UNESP]; de Moura, Márcia Regina [UNESP] (My University, 2024)
The use of edible films has garnered significant interest in the food and environmental sectors due to their potential to prevent food deterioration and their biodegradability. This study aimed to develop and characterize edible films based on camu-camu residue, gelatin, and glycerol, evaluating their solubility, thermal, degradability, antioxidant, and water vapor permeability properties of the gelatin matrix. This is the first study incorporating camu-camu into a gelatin and glycerol matrix. The films produced with camu-camu residue were manageable and soluble, with some non-soluble residues, providing a shiny and well-presented appearance. In the biodegradation results, samples 3 and 4 appeared to degrade the most, being two of the three most affected samples in the triplicate. The films showed degradation modifications from the third day of the experiment. In the germination and plant growth analysis, sample 4 exhibited satisfactory development compared to the other samples, emerging as the sample with the best overall result in the analyses, attributed to a 13.84 cm increase in the growth of the upper part of the seedling. These results indicate that the produced materials have potential for food packaging applications.
Keywords: antioxidants; biodegradable; gelatin; glycerol; Myrciaria dubia (H. B. K.) Mcvaugh